Kansei Engineering Concept in Instructional Design : A Novel Perspective in Guiding the Design of Instructional Materials - Kee, Man Chuah; Chwen, Jen Chen; Chee, Siong Teh (Fifth International Cyberspace Conference on Ergonomics, 2008)
Kansei Engineering is a proven methodology for translating human feelings into a product design. It is capable of enhancing users’ satisfaction on a product by analyzing the relationships between their feelings and design parameters. Though it has been widely implemented on consumer and industrial products, its use on instructional materials remains a potential domain to be explored and examined. Furthermore, in recent years, instructional designers have paid increasing attention to affective issues in improving learners’ learning experience. Thus, this paper offers a fresh perspective by integrating Kansei Engineering methodology in the instructional design process. In particular, it describes how Kansei Engineering methods can be used to elicit important design elements of instructional materials that would in turn induce positive emotions on the learners and optimize effective learning.